Improving Seventh Grade Students’ Vocabulary Using Flash Card at SMPN 2 Pulau-Pulau Aru - Ngosiem, Maria Jomima; Maruanaya, Hendrik; Tanasale, Inggrit (MATAI: International Journal of Language Education, 2023)
This research endeavors to enhance students' vocabulary through the innovative use of flashcards as a teaching tool. Employing a collaborative Classroom Action Research (CAR) approach, the study engaged 19 seventh-grade students from VII.2A at SMP N 2 Pulau-Pulau Aru. Over a span of six sessions encompassing two cycles, the research gathered and analyzed two sets of data—tests and questionnaires—administered to the students. The analysis of these datasets revealed noteworthy insights. Initially, during cycle one, the treatment exhibited minimal progress in specific areas. However, after refining particular aspects in cycle two, substantial improvement was observed. Consequently, it is conclusive that there was a significant enhancement in students' vocabulary proficiency through the use of flashcards. This was evidenced by the test analysis, indicating an increase from 3.16% in cycle one to an impressive 22.11% in cycle two. Additionally, students' responses in the questionnaires provided valuable insights. Notably, 14.66% of students strongly agreed, while 4.13% agreed with the teaching approach. Intriguingly, there were no indications of disagreement among the students. Notably, 67% of the data emphasized that utilizing flashcards greatly aided students in memorizing and comprehending concrete, countable nouns taught during the sessions. This robustly supported the effectiveness of flashcards in facilitating a deeper understanding of vocabulary.